Realisme Magis dalam Novel Intelegensi Embun Pagi Karya Dee Lestari - Minarni Minarni; Arisa Arisa; Ahmad Ghazali Samad; Amirah Akifah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to examine and describe magical realism in the novel Inteligensi Embun Pagi by Dee Lestari using the framework of magical realism proposed by Wendy B. Faris. According to Faris, magical realism consists of five characteristics: (1) the irreducible element, (2) the phenomenal world, (3) unsettling doubts, (4) the merging of realms, and (5) disruptions of time, space, and identity. The data in this study consist of words, phrases, sentences, expressions, and paragraphs that contain elements of magical realism. The data source is the novel Inteligensi Embun Pagi by Dee Lestari. This research employs a qualitative descriptive method, with data collection techniques involving reading and note-taking. The results of the study indicate that there are narrative elements reflecting magical realism based on Wendy B. Faris’s framework in the novel Inteligensi Embun Pagi, including irreducible elements, the phenomenal world, unsettling doubts, the merging of realms, and disruptions of time, space, and identity. Furthermore, the findings reveal that the novel Inteligensi Embun Pagi, when analyzed through Faris’s magical realism perspective, is closely related to magical elements. This is evident in the presence of magical objects, characters, and events, such as characters possessing particular powers, the appearance of figures from other dimensions, and events that are difficult to accept through human rationality.